2021
DOI: 10.1155/2021/6656080
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Suppression Taurine on Relocation and Epithelial-Mesenchymal Transition in Mankind Lung Cancer Cells

Abstract: Aim. Taurine is believed to have antioxidant properties and has been implicated in the treatment of neurodegenerative disease, atherosclerosis, coronary heart disease, and prostate cancer. This research focused on taurine inhibition effects of expression related to migration and epithelial-mesenchymal transition- (EMT-) A549 study on related genes of human being non-small-cell lung cancer. Methods. MTT assays assessed cell viability and a RadiusTM assay showed that taurine also inhibited the lung cancer cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Natural compounds with antioxidant activity and low cytotoxicity give rise to a new era of research where they can cure and treat cancer and other associated diseases. Previous studies have reported that taurine can be used to treat cancer, , but the inhibition of expression and activity of CDK6 by taurine provides a novel avenue for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds with antioxidant activity and low cytotoxicity give rise to a new era of research where they can cure and treat cancer and other associated diseases. Previous studies have reported that taurine can be used to treat cancer, , but the inhibition of expression and activity of CDK6 by taurine provides a novel avenue for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous metabolomic studies on thyroid nodules found that compared with benign nodules, the contents of lactic acid and taurine were increased in malignant thyroid nodules [ 39 , 42 , 44 ]. Taurine is believed to have antioxidant properties and has been implicated in the treatment of neurodegenerative disease, atherosclerosis, coronary heart disease, and prostate cancer [ 45 , 46 ]. It has also been found that taurine can inhibit tumor cell proliferation, enhance apoptosis, inhibit angiogenesis and play an anti-tumor role [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine, as conditionally essential amino acid of human, has multiple physiological functions, including the regulation of neural conduction, participating in endocrine activities, immunity enhancement, and strengthening the antioxidant capacity of cytomembrane ( 35 ). Taurine was found to inhibit the proliferation of lung cancer cells, significantly boosted the apoptosis rate, and reduced the expression of migration factors matrix metallopeptidase 9 (MMP-9) and vascular endothelial growth factor (VEGF) ( 36 , 37 ). Previous studies have shown that taurine ABC transporter protein has been identified in Lactobacillus , and this could have something to do with the enrichment of Lactobacillus in controls of our study ( 38 ).…”
Section: Discussionmentioning
confidence: 99%